Perspectives of clinical microbiologists on antimicrobial stewardship programmes within NHS trusts in England. Issue 1 (December 2015) - Bailey, Chantelle; Tully, Mary; Cooke, Jonathan
Abstract Background The Antimicrobial Self-Assessment Toolkit for NHS Trusts (ASAT) was developed in England by a National Pharmacist Reference Group of an Advisory Non-Departmental Public Body on Antimicrobial Resistance and Healthcare Associated Infections (ARHAI), in conjunction with the Department of Health. It is intended to identify and evaluate interventions for the promotion and implementation hospital-based antimicrobial stewardship programmes (ASPs). ASAT v16 was produced by iterative validity testing with end-users utilising a sequential exploratory strategy. It was highlighted that there was a need for the inclusion of the domain which targeted the role of clinical microbiologists due to their substantial roles in hospital-based ASP development and implementation. Methods This study aimed to investigate the content validity of ASAT v16 and a proposed draft domain for clinical microbiologists and hence produce ASAT v17. From June to September 2011, semi-structured interviews were conducted with ten consultant clinical microbiologists from secondary and tertiary care National Health Service (NHS) Trusts within England. Interviews were conducted until no novel themes were identified i.e., data saturation was achieved. Each interview was digitally recorded and transcribed verbatim and then analysed using a thematic framework that facilitated the identification of emergent themes and sub-themes. Results Nine emergent themes were identified which included common enablers and challenges associated with the implementation of effective and sustainable hospital-based ASPs. Key themes included formal governmental mandates, IT infrastructure and also prescribers' knowledge base of antimicrobial chemotherapy and infectious diseases. Most respondents agreed with the content of ASATv16 and the proposed draft section however they suggested that minor modifications were required to improve question sensitivity and hence reduce measurement error. Conclusions Although, the ASAT been through multiple iterations and content validity testing, further modifications were required to produce the next iteration, ASAT v17. Question merging and other minor modifications were conducted as indicated by study findings. This study reinforces the need for stakeholder engagement during the development and implementation of tools that evaluate hospital-based implementation strategies.